Spatial Economic Science New Frontiers in Theory and Methodology - Reggiani, Aura (Advances in Spatial Science, The Regional Science Series, 2000)
This volume aims to provide an overview of new frontiers in theoretical/methodological studies and research applications concerning the space-economy. It is a focussed selection of ideas and reflections put forward by scientists exploring new insights and channels of research, where the quantitative synthesis of spatial systems is the integrative framework. The conclusion drawn from the book is that the fast-changing socio-economic structures and political landscapes are pushing spatial economic science in various "evolutionary" directions. From this perspective, the valuable heritage of the discipline, built up over fifty years, constitutes the solid methodological basis from which to proceed